Regionalism or Multilateralism? : A Political Economy Choice - Albertin, Giorgia (IMF Working Papers; Working Paper ;, 2008)
This paper provides a political economy analysis of the incentives underpinning a country's decision to enter a regional trade agreement when a multilateral free trade agreement is available, and of how entering a regional trade agreement affects the incentives to pursue multilateral trade liberalization. Taking into account the influence exerted by organized interest groups in the formation of trade agreements, we derive a formal condition under which a regional trade agreement is preferred to a multilateral one. Furthermore, we show that a country's decision to enter a regional trade agreement unambiguously undermines the incentives towards multilateral trade liberalization.